Error analysis of mathematics students in solving mathematical finance problems - Intan Sari; Mawarni Mawarni (Universitas Sarjanawiyata Tamansiswa, 2025)
Mathematical Finance is a course in the Mathematics Study Program. This course is highly useful in both the workplace and everyday life. However, the results of the student’s final exams (UAS) show unsatisfactory outcomes. This research is a descriptive qualitative study that aims to identify the types of errors in students' answers when solving Financial Mathematics final exams. The subjects of this research are students in the even semester of the Mathematics study program at Universitas Samudra. The data collection technique in this research is a test. The results showed that the standard errors found in students' answers were concept errors, namely errors due to students not understanding the concept, as well as procedural errors, which occurred when students had difficulty in linking concepts to the steps of the process. Additionally, there is a slip error that occurs when students are in a hurry to solve the problem, although this error is not dominant. This study concludes that a lack of conceptual understanding and procedural mainly causes students difficulties in Mathematical Finance. These findings contribute to the development of effective learning strategies and the creation of teaching materials by emphasizing the importance of understanding concepts and procedures in problem-solving.